Complex nutritional deficiencies in a large cohort of Italian patients with Cornelia de Lange syndrome spectrum. Issue 9 (9th July 2020) - Parma, Barbara; Cianci, Paola; Decimi, Valentina; Mariani, Milena; Provero, Maria Cristina; Funari, Caterina; Tajè, Silvia; Apuril, Erika; Cereda, Anna; Panceri, Roberto; Maitz, Silvia; Fossati, Chiara; et al.
Abstract: Cornelia de Lange syndrome Spectrum (CdLSp) is characterized by intellectual disability, facial dysmorphisms, and growth impairment. Although eating difficulties are a well‐known feature of the disease, there is no data regarding the nutritional deficiencies of these patients. The food intake was tracked using a dietary transcription provided by the family/caregivers, biochemical nutritional parameters were measured with laboratory tests and through an accurate clinical evaluation of the incidence of qualitative and quantitative imbalances in a cohort of 73 patients with CdLSp ware determined. Of these 73, 62 (85%) subjects provided a complete and detailed dietary transcription. In the studied population, a quantitative caloric imbalance in 47/62 (76%) subjects was observed. The caloric intake was low in 27/62 (43%) subjects whereas excessive in 20/62 (33%). Only 15/62 (24%) had an optimum caloric intake. Regarding micronutrients, a calcium intake deficiency in 32% of the patients (20/62) was observed. Blood tests revealed a low iron level in 22/73 (30%) of the patients and 25(OH)D deficiency in 49/73 (67%). Serum hypocalcemia was not evidenced. Qualitative and quantitative imbalances resulted in more frequent than expected in CdLSp patients. A qualitative imbalance was more prevalent in younger patients while in older patients prevailed mainly a quantitative disproportion. We found no statistically meaningful correlation between dietary imbalances, genetic, or clinical parameters. Our findings highlight the need for further studies to evaluate the basal metabolic rate of CdLSp patients and find a correlation with their growth impairment.